Two new genera of Lumbriculidae (Annelida, Clitellata) from North Carolina, USA - Fend, Steven V.; Lenat, David R. (Zootaxa, 2007)
Recent benthic macroinvertebrate collections from North Carolina contained many undescribed oligochaete taxa, mostly belonging to the family Lumbriculidae. Three of the new species had arrangements of spermathecae and atria previously unreported for the family, and were assigned to new two genera. Pilaridrilus is distinguished by the location of spermathecal pores five segments behind the male pores. The single species, Pilaridrilus uliginosus, also has unusually complex penes and spermathecae. Martinidrilus is distinguished by spermathecae beginning more than two segments anterior to the atrial segment, and also by the the vasa deferentia, which join a common duct before joining the atria. The two Martinidrilus species also have unusual digitiform blood vessels in posterior segments. Martinidrilus carolinensis has lateral spermathecae in VI, and Martinidrilus arenosus has dorsolateral spermathecae in VII and VIII. Because arrangement and morphology of reproductive organs do not resemble those of described lumbriculids, the phylogenetic affinities of the new species are not clear. These new genera and species were generally collected from areas of high water quality, suggesting that lumbriculids can be useful in water quality monitoring and conservation evaluation.